Residual effect of sheep manure on lettuce cultivation at different spacings - Vasconcelos, Ubieli Alves Araújo; Costa, Caciana Cavalcanti; Oliveira, Marcela Nobre; Barbosa, José Wilson da Silva; Medeiros, Anderson Barbosa de; Galvão Sobrinho, Thiago (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
A lettuce is one of the most important commercial and consumer stories in the world. This species presents a great response to organic fertilization, being one of the sources of the most pharmacological organic fertilizers in the country's agriculture region, and in the region of the Paraíba hinterland, mainly sheep. The use of adequate spacing and determinant for the production of the product can express its productive potential in the different production systems. With the objective of evaluating the development of the surface in relation to different spacings and the application of doses of sheep manure in subsequent cycles, two experiments were generated during the period from October 2012 to February 2013, in the experimental area of the Federal University of Campina Grande, located in the municipality of Pombal, Paraíba. In each experiment of the current treatments: three spacings (0.20 x 0.20, 0.20 x 0.25, 0.25 x 0.25 m) and four doses of sheep manure (0, 20, 40 and 60 t ha-1). A randomized complete block design was used, with a factorial arrangement of 3 x 4, with three cultivation spaces and four doses of sheep manure, with four replications. The largest treatments that received 60 t ha-¹. The largest treatments that received 60 t ha-¹.